2012
DOI: 10.2174/092986712800099785
|View full text |Cite
|
Sign up to set email alerts
|

ChemoImmunoModulation: Immune Regulation by the Antineoplastic Chemotherapeutic Agents

Abstract: Since 1948, when Farber et al. introduced aminopterin, the first chemotherapeutic agent, more than 100 such agents have come into use. Initially, antitumor chemotherapies were thought to produce only antiproliferative or cytotoxic effects on dividing tumor cells as it was often associated with the damage to healthy tissues and the development of resistant tumor clones. However, that view has been changing as a consequence of recent demonstrations that several antineoplastic drugs, even at low doses, have antia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 100 publications
0
67
0
4
Order By: Relevance
“…In our recent studies, we have shown that the administration of chemotherapeutic drug paclitaxel at ultra-low noncytotoxic doses, previously described as chemoimmunomodulation [106], in healthy C57BL/6 mice significantly reduced the amount of CD11b + Gr1 + immature myeloid cells [107] that are known as an MDSC counterpart in normal mice [28]. Such MDSC down-regulation was associated with increased natural killer cell frequencies in the bone marrow and their ability to produce IFN-γ.…”
Section: Inhibiting Immunosuppressive Functions Of Mdscsmentioning
confidence: 99%
“…In our recent studies, we have shown that the administration of chemotherapeutic drug paclitaxel at ultra-low noncytotoxic doses, previously described as chemoimmunomodulation [106], in healthy C57BL/6 mice significantly reduced the amount of CD11b + Gr1 + immature myeloid cells [107] that are known as an MDSC counterpart in normal mice [28]. Such MDSC down-regulation was associated with increased natural killer cell frequencies in the bone marrow and their ability to produce IFN-γ.…”
Section: Inhibiting Immunosuppressive Functions Of Mdscsmentioning
confidence: 99%
“…However, recent research efforts present compelling evidence that suggests that these same drugs given in low or ultra-low doses may also hold clinical utility through their ability to promote antitumor immunity [2]. If successful, employing these drugs in such a manner would allow for prevention of the significant morbidity associated with current chemotherapy regimens as well as potentially abrogate the potential for the development of tumor resistance.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has been increasing interest in the application of traditional chemotherapeutic agents for the purpose of manipulating the immune system to produce favorable antitumor immune responses using low-dose chemotherapy ("immunogenic" chemotherapy) [11] or even ultralow doses of chemotherapeutic agents, a term coined "chemoimmunomodulation" [2]. It is clear that there is significant interaction between chemotherapeutic drugs, dying tumor cells, and local immune cells that have various effects on tumor immunogenicity, and many of these effects have been previously described using traditional, MTD drug regimen strategies [12].…”
Section: Low Dose Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the myelosuppressive effect of several drugs is well described. [6][7][8][9][10] As recently reviewed by Shurin et al 10 the main immunosuppressive effect of high dose chemotherapy is the depletion of T lymphocytes. Both CD4þ and CD8þ are affected by cytotoxic drugs but the normal levels of peripheral CD4þ cells are more slowly restored than CD8þ.…”
Section: Conventional Chemotherapymentioning
confidence: 99%